Air dry density and quantitative features of conduction xylem elements in 10 species of Malvaceae in Venezuela - Uzcátegui Rojas, Mariangel (2021)
This research is about the relation between air dry density and quantitative features of vessels (frequency and diameter, lumen area) for ten species of Malvaceae from Venezuela: Catostemma commune, Eryotheca globosa, Ochroma pyramidale, Pachira quinata, Guazuma ulmifolia, Apeiba tibourbou, Heliocarpus americanus, Uladendron codesurii, Sterculia apetala and Sterculia pruriens. Density was determined in samples with moisture content equal to 12 % and measures of vessels features were realized in slides samples of cross sections using standards procedures in xylem microtechnique. Higher vessels frequencies and lower diameters were observed in Guazuma ulmifolia and Uladendron codesurii and lower frequencies and higher diameters were observed in species from Bombacoideae and Sterculioideae subfamilies. Air dry density shows a high variation, ranging from very low density (Ochroma pyramidale, Pachira quinata, Apeiba tibourbou, Heliocarpus americanus, Sterculia apetala) to very high density (Uladendron codesurii). A low correlation between density and vessels features was found and its possible that others wood anatomy features have a higher effect over wood density for Malvaceae.